2022
DOI: 10.1177/14574969221083133
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of femoral fractures in children and adolescents in Finland and Sweden between 1998 and 2016: A binational population-based study

Abstract: Background and objective: Femoral fractures in children have significant impact for patients, family, and trauma resources as they usually require hospitalization and surgical treatment. The aim of this study was to determine the incidence and trends of femoral fractures among children and adolescents hospitalized between 1998 and 2016 in Finland and Sweden. Methods: All patients younger than 17 years of age in Finland and Sweden with a femoral fracture treated surgically between 1998 and 2016 were included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…MDJ is a special area of the distal femur, and in our study, MDJ fractures accounted for 12.1% of all femoral fractures, which was lower than the incidence of distal femoral fractures reported in the past. Salonen et al [ 3 ] reported that distal femoral fractures occurred most frequently at less than 1 year old and between 12 and 16 years old, with the lowest incidence for children aged between 1 and 6 years old. In contrast, the average age of patients with distal MDJ fractures of femur in our study was 7 years old, mostly under 6 years old (69.7%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MDJ is a special area of the distal femur, and in our study, MDJ fractures accounted for 12.1% of all femoral fractures, which was lower than the incidence of distal femoral fractures reported in the past. Salonen et al [ 3 ] reported that distal femoral fractures occurred most frequently at less than 1 year old and between 12 and 16 years old, with the lowest incidence for children aged between 1 and 6 years old. In contrast, the average age of patients with distal MDJ fractures of femur in our study was 7 years old, mostly under 6 years old (69.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Femoral fracture is a common trauma in children, with an incidence of about 14-20/100,000 [ 1 ]. However, distal femoral fractures are rare injuries which account for 18% to 31% of all femoral fractures [ 2 , 3 ]. The peak incidence is between 10 and 12 years of age and more common among males [ 4 ], and the most common mechanisms of injury are sports activities and motor vehicle accidents.…”
Section: Introductionmentioning
confidence: 99%
“…12 Statistical analyses were performed similarly to our previous trauma register-based study in femoral childhood fractures. 3 To calculate the incidence rates of femoral diaphyseal fractures, the annual mid-year population of Finland was obtained from Statistics Finland, which serves as an electronic national population register. 13 The annual incidences per 100,000 persons were calculated using annual mid-year population census data obtained from Statistics Finland.…”
Section: Methodsmentioning
confidence: 99%
“… 1 , 2 Based on our recent research, the incidence of femoral fractures in Finnish children younger than 17 was 13.3 per 100,000 persons, and around 70% of pediatric patients with femoral fractures were boys. 3 The majority of femoral fractures were located on the femoral shaft, with an incidence of 11.6 per 100,000 persons in boys and 3.5 per 100,000 persons in girls aged 1–7. In children aged 7–12 years, the corresponding incidences were 12.7 and 4.8 per 100,000 persons, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation